2018
DOI: 10.1017/s0022215118001767
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of nasal functions and their relationship with cholesteatoma formation in patients with unilateral chronic otitis media

Abstract: ObjectivesTo evaluate the nasal functions of patients with unilateral chronic otitis media using rhinomanometry, comparing chronic otitis media sides with healthy sides, chronic otitis media patients with cholesteatoma and without cholesteatoma, and patients with healthy individuals.MethodsThis prospective study included 102 patients with unilateral chronic otitis media (48 with and 54 without cholesteatoma). The control group comprised 40 individuals without any ear or nasal pathologies. All patients underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Watson et al 6 determined by anterior active rhinomanometry that in a sample of 15 patients with COM the nasal resistance on the side of the affected ear was significantly greater than in controls. But, using the same technique, Arsla et al 8 did not find significant differences in nasal airway resistance between the COM sides and unaffected sides between 102 patients with unilateral COM and 40 individuals without any ear or nasal pathologies controls. And Toros et al 10 did not observe correlation between the ear with COM and the side of nasal obstruction by acoustic rhinometric in a sample of 55 patient with COM.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Watson et al 6 determined by anterior active rhinomanometry that in a sample of 15 patients with COM the nasal resistance on the side of the affected ear was significantly greater than in controls. But, using the same technique, Arsla et al 8 did not find significant differences in nasal airway resistance between the COM sides and unaffected sides between 102 patients with unilateral COM and 40 individuals without any ear or nasal pathologies controls. And Toros et al 10 did not observe correlation between the ear with COM and the side of nasal obstruction by acoustic rhinometric in a sample of 55 patient with COM.…”
Section: Discussionmentioning
confidence: 91%
“…However, the relationship between the nose conditions and COM is controversial. While some authors have found a significant correlation between the incidence of nasal pathology and COM, 4–7 others do not find such a correlation 8–11 . Regardless of the role of alterations of the nose and/or nasopharynx on the middle ear, the intimate knowledge of this relationship would be of great interest for the treatment of patients with COM and concomitant nasal and/or nasopharyngeal alterations, a very common situation in the clinical practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation